An exploration of community development higher education in the United States: A programmatic study. Issue 4 (8th August 2021) - Hains, Kristina D.; Rios, Michael; Hains, Bryan J.; Koundinya, Vikram; Abrams, Carolyn; Stanard, Virginia
ABSTRACT: The field of community development has grown substantially over the past few decades. This is characterized by an increased demand for professionals who can engage in community development efforts and assist in establishing impactful solutions to community issues. This increased demand has created a need for robust Community Development Education programs in higher education to educate community development practitioners. However, due to the minimal interaction between community development educators, historically there has been very little consensus about the fundamental skills, knowledge and pedagogy necessary for the development of community change agents. Therefore, a foundational national study was undertaken to document undergraduate and graduate community development programs in higher education across the United States. Results identified 107 Community Development Education programs and outlined baseline program demographics. Future directions and implications for the field are also provided.